Education and Mental Health:: Labour in the educational nursery of CAPS AD III regional in ANÔNIMO/PR - Deitos, Juliano Marcelino; Nunes de Almeida, Delfino (Brazilian Journal of Mental Health, 2024)
This report highlights an experience of mental health education carried out at CAPS AD III Regional in Coronel Vivida/PR. It is about the proposition and development of an Educational Nursery that prioritized as a methodology the realization of Labour, in its ontological, sense associated with the Healing Garden perspective, aiming the construction of a Singular Therapeutic Project (PTS). The proposal starts from the elaboration of a set of multidisciplinary therapeutic approaches that are articulated and directed under the principles of the Anti-asylum Brazilian Psychiatric Reform. The adopted strategy promoted educational principles focused on autonomy, self-government and self-confidence.